In vitro studies on the cytotoxicity, and elastase and tyrosinase inhibitory activities of marigold (Tagetes erecta L.) flower extracts - Omboon Vallisuta (2018)
Marigold (Tagetes erecta L.) has long been used as a medicinal herb for a number of therapeutic activities. In the present study, the cytotoxicities of ethanol and ethyl acetate extracts of marigold flowers and their inhibitory effects on elastase and tyrosinase enzymes were investigated. An MTT assay was performed to measure the cytotoxicity of these two extracts on the H460 lung cancer and the Caco-2 colon cancer cell lines. An elastase assay kit, based on the digestion of a non-fluorescent elastin substrate to highly fluorescent fragments by elastase, was used for the elastase inhibition assay. Tyrosinase inhibition activity was investigated using the dopachrome method with L-3,4-dihydroxyphenylalanine (L-DOPA) as a substrate. The data obtained in this study demonstrated that the extracts were nontoxic to H460 and Caco-2 cell lines. The elastase inhibition activities of ethanol (250 μg/ml) and ethyl acetate (125 μg/ml) extracts were found to be significantly higher than that of the negative control. The tyrosinase inhibition activities of ethanol and ethyl acetate extracts, in terms of the mean inhibition concentration (IC50), were 1,078 and 1,467 μg/ml, respectively. To the best of our knowledge, the present study has demonstrated for the first time that marigold flower extracts possess tyrosinase inhibition activity. The activities of ethanol and ethyl acetate extracts of marigold flowers were investigated in vitro and indicated that these extracts possess useful properties that may be of interest for cosmetic development.